A Review of Microalgal Biofilm Technologies: Definition, Applications, Settings and Analysis - Moreno Osorio, Jairo Hernán; Pollio, Antonino; Frunzo, Luigi; Lens, Piet Nicolaas Luc; Esposito, Giovanni (Frontiers in Chemical Engineering, 2021)
Biofilm-based algal cultivation has many advantages over the conventional suspended growth methods and has received increased attention as a potential platform for algal production, wastewater treatment (nutrient removal), and a potential pathway to supply feedstock for microalgae-based biorefinery attempts. However, the attached cultivation by definition and application is a result of a complex interaction between the biotic and abiotic components involved. Therefore, the entire understanding of the biofilm nature is still a research challenge due to the need for real-time analysis of the system. In this review, the state of the art of biofilm definition, its life cycle, the proposed designs of bioreactors, screening of carrier materials, and non-destructive techniques for the study of biofilm formation and performance are summarized. Perspectives for future research needs are also discussed to provide a primary reference for the further development of microalgal biofilm systems.